Female Sexual Function and Dysfunction - Costantini, Elisabetta; Villari, Donata; Filocamo, Maria Teresa (Springer International Publishing : Imprint: Springer, 2017)
This book discusses all aspects of sexuality in women and in particular explores sexual function and dysfunction in a variety of settings, including the different stages of life and a wide range of major diseases and local conditions. The aim is to refocus attention on the needs and sexual realities of women, providing a fresh point of view that will assist gynecologists, sexual medicine physicians, and urologists in delivery of high-quality care and help women themselves to understand and address sexual problems relating to desire, arousal, orgasm, and sexual pain. Psychological aspects of female sexuality and the impacts of the aging process, pregnancy, and childbirth are carefully examined. Extensive consideration is then given to the effects on sexual function of such conditions as cardiovascular disease, cancer, diabetes, neurological disease, endometriosis, pelvic organ prolapse, urinary incontinence, reproductive disorders, sexual abuse, and drug abuse. Issues of sexual identity and female dysmorphophobias are also considered. The authors are all experts in the field and have a deep understanding of the complexities of female sexuality. .
Keywords: Medicine.; Gynecology.; Urology.; elektronické knihy; electronic books